EXAMINING GUIDED NOTE TAKING METHOD TO ASSIST LISTENING SKILL AT MADRASAH ALIYAH ARRISALAH CURAH KATES AJUNG - Mahbubah, Laili; Al Fauzi, Fatih; Basya, Dihliza (E-Link Journal, 2019)
The researcher decide to conduct a research about examining guided note taking method to assist listening skill by the research problem: how can guided note taking can assist their achievement in listening skill at Madrasah Aliyah Arrisalah Curah Kates Ajung. The design in this research is Classroom Action Research (CAR). The subject of the research is X grade of Aliyah Arrisalah Curah Kates Ajung in the 2018/2019 academic years which consist of 25 students in a class. The research was done on 2 28 February 2019. The data was mainly obtained through test. The test is objective matching from the text. The data was analyzed using formula E = n / N x 100%. The result of the score of the analysis, the percentage of the students who got > 70 was 40% in cycle 1 and 76% in cycle 2. The way that researcher used to assist the students listening comprehension is by modificating audio-visual media. So the guided note taking will help the students organize their idea, focus the energy, create and empty space in braind and make the students be confident. Guided note taking can increase their stock of knowledge to the students.Key Words : Listening Skill, Guided Note Taking Method